MSI-based polycyclic and heterocyclic aromatic hydrocarbons (PAHs and C2-DBF) in the uppermost Permian Changxing Fm. in the Meishan C section - Ryosuke Saito; Lars Wörmer; Heidi Taubner; Kunio Kaiho; Satoshi Takahashi; Li Tian; Masayuki Ikeda; Roger E Summons; Kai-Uwe Hinrichs (PANGAEA, 2022)
A 7T solariX XR Fourier transform-ion cyclotron resonance-mass spectrometer (FT-ICR-MS) equipped with a Smartbeam II laser (Bruker Daltonik, Bremen, Germany) was used for MSI analysis. Analyses were carried out in positive ion mode in a range of 150-750 Da. A defined area of the sample was scanned by the laser with a distance of 100 μm between spots. Laser power, frequency and number of shots per spot were adjusted for optimal signal intensities. PAHs and C2-DBF were identified based on their monoisotopic mass. Internal mass calibrated results were exported from DataAnalysis 4.4. SR1 (Bruker Daltonik) and further processed in MATLAB R2015b using a DataAnalysis Script File.
In: Saito, R et al. (2022): An expanded record of proxy data in the uppermost Permian Changxing Fm. in the Meishan C section [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.952297